2020
DOI: 10.18203/2349-3259.ijct20201714
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of haemodynamic responses to endotracheal extubation-diltiazem versus lidocaine

Abstract: <p class="abstract"><strong>Background:</strong> Endotracheal extubation is one of the frequently performed procedure in the practice of anaesthesia. This study was done to observe the haemodynamic responses during tracheal extubation and to compare the efficacy of IV diltiazem 0.2 mg/kg versus IV lidocaine 1 mg/kg in attenuating the hemodynamic response to tracheal extubation.</p><p class="abstract"><strong>Methods:</strong> 90 patients aged 20 to 60 yrs, belonging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Intravenous lignocaine with its well established centrally depressant and antiarrhythmic effect was found to be a more suitable alternate method to minimize this pressor response [8]. Recently several studies have shown that calcium channel antagonist like diltiazem, with its direct vasodilation and direct negative chronotropic and dromotropic properties is also effective [5,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous lignocaine with its well established centrally depressant and antiarrhythmic effect was found to be a more suitable alternate method to minimize this pressor response [8]. Recently several studies have shown that calcium channel antagonist like diltiazem, with its direct vasodilation and direct negative chronotropic and dromotropic properties is also effective [5,6,9].…”
Section: Introductionmentioning
confidence: 99%